The Effect of Workload and Work Stress on Employee Job Satisfaction on Lucky Plaza Batam Cellular Data Store - Elfina, Rini; Moein, Anoesyirwan; Zen, Yuli (MultiTech Publisher, 2024)
The purpose of this study is to ascertain how work stress and workload affect employee satisfaction at the HP secular Lucky Plaza Batam store. Situated at Jl. Imam Bonjol, Lubuk Baja Kota, Lubuk Baja District, Batam City, Riau Islands, the HP secular Lucky Plaza Batam Store served as the research site for this study. Researchers use a quantitative population. Up to 50 employees of the HP Secular Lucky Plaza Batam Store work in this area. Research findings indicate that workload has an impact on job satisfaction among employees at the HP Secular Lucky Plaza Batam Store. Stress at work has an impact on job satisfaction at the HP secular Lucky Plaza Batam Store. Stress at work and workload at the same time affect Job Satisfaction at HP secular Lucky Plaza Batam Store.